ANALISA KELENGKAPAN RESUME MEDIS (DISCHARGE SUMMARY) DI RUMAH SAKIT MEILIA CIBUBUR - N Aal Siti Alawiah; Dina Sonia (Bajang Institute, 2021)
Medical Record is a file containing records and documents about patient identity, examination, treatment, other service actions that have been given to patients. Medical resume is a summary of the entire period of care and treatment of patients carried out by doctors to patients. The completeness of the medical resume is a reflection of the quality of medical records and services provided by the hospital. This study aims to describe the completeness of the medical resume of outpatients at Meilia Hospital. The research method used is by using observation techniques. The population of the data is medical records of inpatients of 81 medical records obtained from the results of calculations using the Slovin formula from the research conducted, the following results were found: that the population of incomplete medical resumes at Meilia Cibubur Hospital reached 27% and completeness of medical resumes at the Hospital Meilia Cibubur reached 73%. The conclusion that can be drawn from this research is that the analysis of the completeness of the inpatient medical resume has gone well, suggestions need to be re-socialized for the importance of authentication in writing and completing the medical resume because it is related to legal aspects, and sanctions are given if the doctor is not disciplined in filling out the medical resume